Tinjauan Hukum Islam terhadap Praktik Multiakad dalam Produk Tabungan Pendidikan - Rusmalana; Hendra Karunia Agustine (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2026)
The multi-contract (multiakad) approach has become one of the methods used to develop products in Islamic banking. This practice stems from innovation as a form of ijtihad in muamalah transactions currently implemented in the industry. One Islamic banking product applying the multi-contract concept is the educational savings scheme at Bank Syariah Indonesia, Kuningan Sub-Branch Office (BSI KCP Kuningan). The issue, however, is that the permissibility of multi-contracts is not without limits; certain boundaries must be observed to avoid elements of riba (usury), gharar (uncertainty), and maisir (gambling). This study aimed to examine the multi-contract mechanism within BSI KCP Kuningan’s educational savings product and to review it from the perspective of Islamic law. Employing a qualitative field research design, data were collected through interviews with bank staff and documentation from brochures and articles. The data were then reduced, displayed, and concluded in narrative form. The findings revealed two key points. First, the multi-contract practice in this product involves two contracts with opposing motives: a mudharabah muthlaqah contract, which is business-oriented, and a tabarru contract, representing social (non-commercial) insurance protection. Second, the Islamic legal review indicates that the multi-contract structure in this educational savings product does not fully comply with fiqh muamalah provisions.